2008
DOI: 10.1002/ccd.21759
|View full text |Cite
|
Sign up to set email alerts
|

Early and long‐term results of percutaneous coronary intervention for unprotected left main trifurcation disease

Abstract: Percutaneous treatment of ULM trifurcation disease is feasible, associated with favorable mid-term results, and may be considered given its low invasiveness in patients at high surgical risk or with multiple comorbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…Of note, for double-stent techniques, in concurrence with previous reports (3,4,9,10,23), DK-crush and T-stenting demonstrated lower scores, as compared with classic crush, culotte, and SKS. This finding may be of interest for the practicing interventionalist.…”
Section: Discussionsupporting
confidence: 89%
“…Of note, for double-stent techniques, in concurrence with previous reports (3,4,9,10,23), DK-crush and T-stenting demonstrated lower scores, as compared with classic crush, culotte, and SKS. This finding may be of interest for the practicing interventionalist.…”
Section: Discussionsupporting
confidence: 89%
“…We presented the hemodynamic effects on drug distribution patterns using a simplified uniform-cell stent design, though our methodology is adaptable to several types of stents with variable design features. Variability in arterial drug distribution due to other geometric and morphologic aspects such as bifurcation angle, arterial taper as well as presence of a trifurcation [32] can also be understood using our computational framework. Further, performance of a candidate DES using other commonly used stenting procedures for bifurcation lesions such as culotte and crush techniques can be quantified based on their resulting drug distribution patterns and this paradigm can also be extended to predict the effectiveness of dedicated bifurcation stents [33], [34].…”
Section: Discussionmentioning
confidence: 99%
“…However, only a few studies, including a small number of cases, have evaluated the safety and efficacy of DES implantation in this subset of lesions [79][80][81][82]. However, only a few studies, including a small number of cases, have evaluated the safety and efficacy of DES implantation in this subset of lesions [79][80][81][82].…”
Section: Data On Drug-eluting Stents In Left Main Coronary Artery Trimentioning
confidence: 99%
“…Furuichi et al reported the outcomes in 13 patients after DES implantation in de novo distal left main trifurcation lesion. The largest experience of stenting for unprotected left main coronary artery trifurcation disease was reported by Sheiban et al [81]. No deaths, Q-wave myocardial infarctions, or stent thromboses (ST) were recorded [79].…”
Section: Data On Drug-eluting Stents In Left Main Coronary Artery Trimentioning
confidence: 99%
See 1 more Smart Citation